Soil organic carbon fractions under conventional and no-till management in a long-term study in southern Spain - Carbonell-Bojollo, R (2015)
In dryland farming systems under a Mediterranean climate, soil quality and productivity can be enhanced by increasing the content of soil organic carbon (SOC) through alternative soil management systems. Some fractions of C are directly involved in increasing total SOC and therefore in enhancing any beneﬁts in terms of soil properties. This study compares the viability of no-till farming (NT) with conventional (traditional) tillage (TT) for improving SOC levels. The inﬂuence of management practices was investigated for different fractions of C (particulate OC, active OC, humic acids, fulvic acids) and CO2 emissions in clayey soils in the south of Spain. The experiment was conducted over three farming seasons (2006–07, 2007–08 and 2008–09) covering a crop rotation of peas (Pisum sativum L.), wheat (Triticum aestivum L.) and sunﬂowers (Helianthus annuus L.). The NT system improved the levels of the different fractions of C in the surface soil and reduced the amount of CO2 released into the atmosphere compared with the TT system. Generally, the relationship between CO2 and SOC content was greater in soils under NT for the farming seasons sampled.